IMPLEMENTASI KEAKTORAN DENGAN TEKNIK BERMAIN DRAMA RENDRA PADA PEMBELAJARAN DRAMA KELAS XI MAN KARANGANYAR TAHUN AJARAN 2012/2013 - Astuti, Laela; Al Ma'ruf, Ali Imron; Ngalim, Abdul (Jurnal Penelitian Humaniora, 2013)
The aimsof this study are (1) to describe the Rendra?s drama techniques, (2) to imple- ment Rendra?s drama acting techniques in drama learning for students of MAN Karanganyar class XI. This is a case study (embedded case study). The data collection technique used is observation and documentatatipon. Data validity used is triangulation of data and theory. Data analysis technique used is descriptive interpretative. The research results indicate that acting and drama playing technique from Renda can be well implemented in drama teaching and learning process in the classroom by adapting less technical direction in accordance with the conditions of the class.